2023
DOI: 10.1371/journal.pone.0288736
|View full text |Cite
|
Sign up to set email alerts
|

Repeat sprint fatigue and altered neuromuscular performance in recreationally trained basketball players

Abstract: The primary aim of the present study was to investigate how the fatigue induced through a repeat sprint protocol acutely affected different measures of neuromuscular performance. Recreationally trained basketball players (n = 25) volunteered to participate in the study, and performed three countermovement jumps (CMJ), as well as three drop jumps (DJ) prior to a fatiguing repeat sprint protocol. These procedures were repeated two minutes, and 15 minutes, following the protocol. Various force-time metrics were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Yoshida et al recently showed that at 6 h following basketball-related high-intensity exercises, moderate to large performance decrements in peak force, flight-time:contraction-time, as well as positive impulse, unweighting impulse, eccentric rate of force development and duration, when compared to baseline ( 41 ). Metrics such as JH or peak power have been shown to be sensitive to fatigue or sport-specific training exposure at timepoints closer to the commencement of the fatiguing activity ( 4 , 24 ). Others have reported opposite or conflicting findings when looking at traditional or outcome-based metrics such as JH ( 4 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida et al recently showed that at 6 h following basketball-related high-intensity exercises, moderate to large performance decrements in peak force, flight-time:contraction-time, as well as positive impulse, unweighting impulse, eccentric rate of force development and duration, when compared to baseline ( 41 ). Metrics such as JH or peak power have been shown to be sensitive to fatigue or sport-specific training exposure at timepoints closer to the commencement of the fatiguing activity ( 4 , 24 ). Others have reported opposite or conflicting findings when looking at traditional or outcome-based metrics such as JH ( 4 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in response to NMF through training and game performance in female basketball players, Spiteri et al proposed that jump height remained relatively unchanged, while jump duration increased, highlighting that flight-time:contraction-time may be a metric suited to study fatigue ( 22 ). On the other hand, others have proposed jump height to be sensitive to acute levels of fatigue ( 23 , 24 ). Further, Spencer et al recently aimed to explain maintenance in jump height following soccer competition through decreases in jump momentum, induced by acute reductions in body weight, which should be factored in when interpreting the acute fatigue response using vertical jump tasks ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…High physical activity will affect the level of physical fatigue. A person with high physical activity will indirectly be easier to level of fatigue, especially physical fatigue (Philipp et al, 2023). Fatigue in sports reduces or weakens a person's ability to perform physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is challenging to specify the exact contribution of each energy source due to different playing styles, it is well-accepted that basketball players primarily rely on the anaerobic metabolism to satisfy on-court competitive demands [1,3,7,9]. Possessing an adequate level of anaerobic power is of critical importance to satisfy the need for rapid force production over a short period of time, when performing repetitive acceleration, deceleration, change in direction, and jumping movements [9][10][11][12]. On the other hand, aerobic capacity is needed to sustain repeated short bouts of high-intensity exercise during the entire game, including both offensive and defensive actions [9].…”
Section: Introductionmentioning
confidence: 99%
“…The countermovement vertical jump is a commonly used testing modality to assess neuromuscular performance and a level of fatigue in sportspecific settings [36,37]. When performed on innovative force plate systems that allow for rapid data analysis, a plethora of performance metrics can be obtained, focused on examining both eccentric and concentric phases of the movement [11,12,[36][37][38][39]. Besides solely being focused on examining jump height as an outcome metric, a detailed examination of force-time variables (e.g., peak concentric force, breaking phase duration, countermovement depth) may help practitioners monitor and quantify recovery-fatigue neuromuscular changes in basketball players to a greater extent [36,37,40].…”
Section: Introductionmentioning
confidence: 99%